The method in science: origin and divergences according to Ruy Pérez Tamayo - Figueroa-Rodríguez, Katia A.; Sangerman-Jarquín, Dora M. (Revista Mexicana de Ciencias Agrícolas, 2022)
Scientists have the challenge of studying different phenomena, this leads them to raise a diversity of questions that are answered using different research methods that also vary depending on the degree of development of each particular area of knowledge. Despite this diversity in science, there is the connotation that there is only one scientific method: the hypothetico-deductive method. This article takes up the work by Ruy Pérez Tamayo: does the scientific method exist? to go through the historical development of various methods and concepts relevant to science with the aim of allowing the reader to have a vision that is holistic but focused on the various methods and tools to do science.
Keywords: hypothetico-deductive method; inductivist method; philosophy of science